2016
DOI: 10.1177/1947603516632848
|View full text |Cite
|
Sign up to set email alerts
|

New Technology in Imaging Cartilage of the Ankle

Abstract: The incidence of osteochondral lesions, as well as osteoarthritis of the ankle joint following osteochondritis dissecans and trauma, has been reappraised in recent years. Consequently, an increasing number of surgical interventions using different cartilage repair techniques is performed in the ankle joint, which has resulted in a growing demand for repetitive and objective assessment of cartilage tissue and its repair. While morphological imaging does enable monitoring of macroscopic changes with increasing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…We used the pairwise t-test for paired and subsequent measurements of the same patient or a knee. Within-individual variation was defined on the basis of the dGEMRIC error rates, which were based on previously published papers, and this indicated that the mean difference per region of interest between the two T1Gd measurements ranged from 3.7% to 6.8% [14,16,18]. Based on this, we defined the arbitrary change of 15% in subsequent measurements as clinically relevant, and considered this as the liminal value (on the basis of two standard deviations from the estimated error rate).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the pairwise t-test for paired and subsequent measurements of the same patient or a knee. Within-individual variation was defined on the basis of the dGEMRIC error rates, which were based on previously published papers, and this indicated that the mean difference per region of interest between the two T1Gd measurements ranged from 3.7% to 6.8% [14,16,18]. Based on this, we defined the arbitrary change of 15% in subsequent measurements as clinically relevant, and considered this as the liminal value (on the basis of two standard deviations from the estimated error rate).…”
Section: Discussionmentioning
confidence: 99%
“…We estimated a percentage change of the dGEMRIC results and estimated the number of clinically relevant improvements vs. deteriorations in each patient ( Figures S1-S10), where a 15% change was considered a relevant change (based on the error rates acquired from the available literature and our studies) [14].…”
Section: Delayed Gadolinium-enhanced Mri Of Cartilage (Dgemric)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used delayed gadolinium (Gd)-enhanced magnetic resonance imaging of cartilage (dGEMRIC) in order to assess proteoglycan synthesis. dGEMRIC is a molecular imaging technique that has been used to study glycosaminoglycan (GAG) loss in the articular cartilage of patients with primary OA [ 25 , 26 ], and it can be readily used on patients with cruciate ligament injury [ 27 , 28 ]. With dGEMRIC, T1-maps of hyaline cartilage are created following the intravenous (IV) administration of an anionic gadolinium-based contrast agent gadopentetate dimeglumine (Gd-DTPA 2− ).…”
Section: Introductionmentioning
confidence: 99%
“…This is the principal difference for increased cartilage degeneration and the high rate of primary OA in the knee. Moreover the cartilage of the ankle is thinner with respect to knee or hip, but owns a higher compressive stiffness, proteoglycan density, lower matrix degradation, and less response to catabolic stimulations (25)(26)(27). (18).…”
Section: Discussionmentioning
confidence: 99%